Lontar Eksistensi Dewata dalam Lontar Tutur Gong Besi: - Budi Adnyana, Gede Agus (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2024)
Lontar Tutur Gong Besi is one of the lontars that has entered Balinese literature, with the classification of lontar tattwa. To find out how the text of the Lontar Tutur Gong Besi and the narrative structure that forms the form of the lontar are literary works. From this narrative structure, the existence of the gods as manifestations of Almighty God will be discovered. This research uses a qualitative descriptive method using the text Lontar Tutur Gong Besi as primary data and other literature that has correlation as secondary data.